BERTRAND MATE OF TIMELIKE BIHARMONIC LEGENDRE CURVES IN LORENTZIAN HEISENBERG GROUP Heis3 - Turhan, Essin; Korpinar, Talat (De Gruyter Poland Sp Zoo, 2011)
In this paper, we study Bertrand mate of timelike biharmonic Legendre curves in the Lorentzian Heisenberg group Heis(3). We characterize timelike biharmonic Legendre curves in terms of their curvature and torsion. Moreover, we obtain the position vectors of timelike biharmonic Legendre curves and we construct parametric equations of Bertrand mate of timelike biharmonic Legendre curves in the Lorentzian Heisenberg group Heis(3).
Keywords: Legendre curve; biharmonic curve; position vector; Heisenberg group